2018
DOI: 10.1186/s13040-018-0181-9
|View full text |Cite
|
Sign up to set email alerts
|

Grasping frequent subgraph mining for bioinformatics applications

Abstract: Searching for interesting common subgraphs in graph data is a well-studied problem in data mining. Subgraph mining techniques focus on the discovery of patterns in graphs that exhibit a specific network structure that is deemed interesting within these data sets. The definition of which subgraphs are interesting and which are not is highly dependent on the application. These techniques have seen numerous applications and are able to tackle a range of biological research questions, spanning from the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…In [20], the authors introduced two potential extensions of the previously mentioned AGraP algorithm, as a means of reducing output set sizes. A new variation of AGraP was proposed (CloseAFG) as well as a new algorithm (IntAFG).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In [20], the authors introduced two potential extensions of the previously mentioned AGraP algorithm, as a means of reducing output set sizes. A new variation of AGraP was proposed (CloseAFG) as well as a new algorithm (IntAFG).…”
Section: Related Workmentioning
confidence: 99%
“…Our proposed FPM algorithm is introduced in Section 4, and our experimental results using it are detailed in Section 5. Our conclusions on applications 22,23 of the proposed algorithm and our thoughts on directions for future work 24,25 are the focus of Section 6.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation of the proteins' spatial shape may provide important functional and structural insights (Clark et al, 1991;Cootes et al, 2003). Indeed, protein structures have been interpreted as graphs of amino acids and studied based on graph theory concepts (Borgwardt et al, 2005;Anchuri et al, 2013;Dhifli et al, 2014;Dhifli and Nguifo, 2015;Dhifli et al, 2017;Saha et al, 2017;Mrzic et al, 2018;Sugiyama et al, 2018). In this regard, some works were interested in the study of protein structures based on their graph properties and involved the use of topological classifications as in Bartoli et al (2007), where it has been shown that proteins can be considered as small-world networks of amino acids.…”
Section: Introductionmentioning
confidence: 99%